Red Hawk and the Sky sisters : a Shawnee legend - Dominic, Gloria, 1950- (Native American lore & legends., 1996)
Relates the story of the skilled hunter Red Hawk who captures and marries the youngest daughter of Bright Star, only to have her return to the sky with their son.